Reactive oxygen species (ROS)-generating oxidases in the normal rabbit cornea and their involvement in the corneal damage evoked by UVB rays - Cejková, J; Stípek, S; Crkovská, J; Ardan, T; Midelfart, A (Histology and histopathology, 2001)
The corneas of albino rabbits were irradiated (5 min exposure once a day) with UVB rays (312 nm) for 4 days (shorter procedure) or 8 days (longer procedure). The eyes were examined microbiologically and only the corneas of sterile eyes or eyes with non-pathogenic microbes were employed. Histochemically, the activities of reactive oxygen species (ROS)-generating oxidases (xanthine oxidase, D-amino acid oxidase and alpha-hydroxy acid oxidase) were examined in cryostat sections of the whole corneas. Biochemically, the activity of xanthine oxidoreductase/xanthine oxidase was investigated in the scraped corneal epithelium. UVB rays significantly changed enzyme activities in the corneas. In comparison to the normal cornea, where of ROS-generating oxidases only xanthine oxidase showed significant activity in the corneal epithelium and endothelium, D-amino acid oxidase was very low and alpha-hydroxy acid oxidase could not be detected at all, in the cornea repeatedly irradiated with UVB rays, increased activities of xanthine oxidase and D-amino acid oxidase were observed in all corneal layers. Only after the longer procedure the xanthine oxidase and D-amino acid oxidase activities were decreased in the thinned epithelium in parallel with its morphological disturbances. Further results show that the xanthine oxidase/xanthine oxidoreductase ratio increased in the epithelium together with the repeated irradiation with UVB rays. This might suggest that xanthine dehydrogenase is converted to xanthine oxidase. However, in comparison to the normal corneal epithelium, the total amount of xanthine oxidoredutase was decreased in the irradiated epithelium. It is presumed that xanthine oxidoreductase might be released extracellularly (into tears) or the enzyme molecules were denatured due to UVB rays (particulary after the longer procedure). Comparative histochemical and biochemical findings suggest that reactive oxygen species-generating oxidases (xanthine oxidase, D-amino acid oxidase) contribute to the corneal damage evoked by UVB rays.
Keywords: rohovkový endotel; Animals; Rabbits; Free Radical Scavengers; rohovka; Alcohol Oxidoreductases; Cornea; časové faktory; Enzyme Inhibitors; Time Factors; Sensitivity and Specificity; Ultraviolet Rays; Reactive Oxygen Species; Xanthine Oxidase; senzitivita a specificita; alkoholoxidoreduktasy; Histocytochemistry; Endothelium, Corneal; scavengery volných radikálů; D-Amino-Acid Oxidase; inhibitory enzymů; histocytochemie; rohovkový epitel; reaktivní formy kyslíku; xanthinoxidasa; králíci; Epithelium, Corneal; zvířata; oxidasa D-aminokyselin; ultrafialové záření